Characteristics of Patients with Autoimmune Rheumatic Disease in the Era of COVID-19 Pandemic in Indonesia - Rudy Hidayat; Harry Isbagio; Anna Ariane; Faisal Parlindungan; Laniyati Hamijoyo; I Nyoman Suarjana; Dwi Budi Darmawati; Rakhma Yanti Hellmi; Gede Kambayana; IA Ratih Wulansari Manuaba; Awalia Awalia (Indonesian Journal of Rheumatology, 2020)
Background Coronavirus Disease 2019 (COVID-19) could be fatal in high-risk patient including autoimmune rheumatic patients. Nowadays, the management of these patients becomes dilemma because the use of steroids and disease-modifying anti-rheumatic drugs could suppress the immune system however, poor control of the underlying disease increases the infection risk. Understanding the characteristics of these patients in the COVID-19 pandemic is essentials to establish management guidelines and identify patients who are more susceptible to COVID-19. This study aimed to determine the characteristics of autoimmune rheumatic patients in the era of COVID-19 pandemic in Indonesia. MethodA descriptive study using national scale survey method was conducted. The subjects were autoimmune rheumatic patients in Indonesia and recruited using consecutive sampling. The variables evaluated in this study were demographic data, history of disease, current medications taken, daily activities in the COVID-19 pandemic, and also data related to COVID-19. The surveys distributed in online form to patients with autoimmune rheumatic disease in Indonesia. ResultTotal participants in this study were 570 patients, mostly women (93.9%), aged <60 years old (97.2%), and diagnosed with systemic lupus erythematosus (62.8%). Glucocorticoid (70.2%) especially low dose glucocorticoid (52.6%) is the most medication taken by patients. A 30.5% of patients is taking hydroxychloroquine/chloroquine and 88.1% of them have good compliance. During COVID-19 pandemic, 76.5% respondents still do normal activities/work and only 53.2% use personal protective equipment. Eleven of 541 respondents had positive PCR test and confirmed to COVID-19. The risk of COVID-19 infection based on British Society of Rheumatology (BSR) scoring system showed that 57.9%, 28.6%, and 13.5% patients in high, moderate and low risk, respectively. ConclusionPatients with autoimmune rheumatic diseases might be more susceptible to COVID-19 than the general population. Interplay of aging, therapies and disease-specific factors, comorbidities and the proper use of personal protective equipment seem to contribute. Keywords :autoimmune rheumatic disease, characteristic, COVID-19, Indonesia